GARCINIA KOLA SEEDS: IS THE AQUEOUS EXTRACT A TRUE APHRODISIAC IN MALE WISTAR RATS? - Yakubu, M T; Quadri, A L (African Journal of Traditional, Complementary and Alternative Medicines, 2021)
The age long acclaimed aphrodisiac potentials of Garcinia kola seeds in some parts of Western Nigeria has not been substantiated with scientific evidence. In this study, we have decided to evaluate the effect of aqueous seed extract of G. kola at the doses of 25, 50 and 100 mg/kg body weight on sexual behaviour of male rats. Male rats weighing 215.00 ± 18.58 g were randomized completely into four groups (A-D) of six animals each. Animals in group A received, orally, 0.5 ml of distilled water only while those in groups B, C and D received same volume containing 25, 50 and 100 mg/kg body weight of the seed extract respectively. Frequencies of mount (MF), intromission (IF), genital toilet (GTF) and ejaculation (EF) as well as latencies of mount (ML), intromission (IL) and ejaculation (EL) were evaluated following the pairing of male rats (1:1) with non-oestrous female rats. The parameters were monitored for the first (15-30 min), second (75-90 min) and third (180-195 min) observatory periods. The levels of testosterone, luteinizing (LH) and follicle stimulating hormones (FSH) were also determined. Phytochemical screening of the extract revealed the presence of saponins (2.78%), cardiac glycosides (0.26%), cardenolides and dienolides (0.24%), flavonoids (1.28%) and steroids (1.14%). The 25 and 100 mg/kg body weight increased (P<0.05) the MF whereas the ML was decreased by all the doses of the extract. MF and ML were not altered during the second observatory period whereas the 50 mg/kg body weight increased these parameters during the third observatory period. Other sexual behaviour parameters as well as serum testosterone, FSH and LH were not significantly altered throughout the observatory periods. Overall, the results revealed that G. kola seeds did not have sex enhancing potential as claimed. Therefore, the acclaimed pro sexual effect of Garcinia kola seeds is scientifically untrue. This study has refuted the claim that one of the rationales for consuming the seeds by the aged population of Nigeria is to enhance sexual invigoration in males.